Two Sports, Two Systems, One Goal: A Comparative Study of Concussion Policies and Practices of the Australian Football League and Hockey Canada - Greenhow, Annette; Doherty, Alison (Frontiers in Sports and Active Living, 2021)
Concussion in sport is today regarded as both a public health issue and high profile injury concern in many contact and collision sports. This paper undertakes a comparative review of the current policies and practices of two high profile national sporting organisations of such sports—the Australian Football League (AFL) and Hockey Canada (HC)—in governing the issue as a regulatory concern. By examining the policies and practices of the AFL and HC, this study aims to identify common themes, divergent practices, and nuanced sport-specific approaches to develop understandings on the regulation and governance of this high profile sports injury. The paper aims to contribute to understanding concussion as a regulatory concern, while at the same time recognising the heterogeneity of sport and reinforcing nuanced understandings that align to specific social and cultural settings. We make recommendations based on regulatory and cultural legitimacy. The paper concludes that these NSOs are institutional actors with historical and cultural roots who assert regulatory legitimacy by steering and influencing behaviour and directing the regulatory agenda to manage and mitigate the harm associated with concussion.